(untitled) (Jurnal Manajemen dan Kewirausahaan, 2014)
This paper aimed to evaluate perfomance of property and real estate companies listed in Indonesia Stock Exchange using the DEA method. Samples were 23 companies listed from 2009–2012. Results showed that some companies are relatively efficient each year. However, only one company consistently had technical efficiency equal to 1. The main cause of inefficiency from 2009–2011 was scale inefficiency while inefficiency happened in 2012 was pure technical inefficiency. Overall the companies operate efficiently un-der constant returns to scale is showing an increase from 17.39%–39.13%.